2015
DOI: 10.7314/apjcp.2015.16.14.6111
|View full text |Cite
|
Sign up to set email alerts
|

XRCC1 Gene Polymorphism, Clinicopathological Characteristics and Stomach Cancer Survival in Thailand

Abstract: Background: Stomach cancer is one of leading causes of death worldwide. In Thailand, the incidence and mortality of stomach cancer are in the top ten for cancers. Effects of DNA repair gene X-ray repair cross complementary protein 1 (XRCC1) polymorphisms and clinicopathological characteristics on survival of stomach cancer in Thailand have not been previously reported. The aim of this study was to investigate the effects of XRCC1 gene and clinicopathological characteristics on survival of stomach cancer patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In Arg399Gln SNP analysis, the variant 399Gln allele frequency was slightly higher in GIC (37.2%) when compared to controls (37.0%) in the present study. Interestingly, the 399Gln allele frequency was found higher when compared to those GIC cases reported in Egyptian, Han Chinese, Japanese, Korean and Western Mexican populations (Abdel-Rahman et al, 2000;Hong et al, 2005;Muñiz-Mendoza et al, 2012;Yin et al, 2012;Gao et al, 2014;Yun et al, 2015) but was lower to Thai population (Putthanachote et al, 2015). Difference in distribution of variant allele in both SNPs among studies indicates that there is a need to clarify the allele distribution of different populations for more precise risk estimation of XRCC1 SNPs towards GIC.…”
Section: Discussionmentioning
confidence: 90%
“…In Arg399Gln SNP analysis, the variant 399Gln allele frequency was slightly higher in GIC (37.2%) when compared to controls (37.0%) in the present study. Interestingly, the 399Gln allele frequency was found higher when compared to those GIC cases reported in Egyptian, Han Chinese, Japanese, Korean and Western Mexican populations (Abdel-Rahman et al, 2000;Hong et al, 2005;Muñiz-Mendoza et al, 2012;Yin et al, 2012;Gao et al, 2014;Yun et al, 2015) but was lower to Thai population (Putthanachote et al, 2015). Difference in distribution of variant allele in both SNPs among studies indicates that there is a need to clarify the allele distribution of different populations for more precise risk estimation of XRCC1 SNPs towards GIC.…”
Section: Discussionmentioning
confidence: 90%
“…It has been postulated that many factors can result in malignant neoplasms. In recent decades, many researchers drew attention to the association between genetic polymorphisms and cancer susceptibility [ 42 , 43 ]. Since then, SNP has been found contributed to the incidence of cancer [ 44 ], including PCa.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results are obtained by Zheng et al [46] that miRNA-192 plays an oncogenic role in colon cancer, and simvastatin inhibits cancer cell growth by activating miR-192. Li et al [47] found that downregulation of miR-181a-5p is observed in aggressive breast and colon cancers, and it inhibits the migration and angiogenesis via downregulation of MMP14; furthermore, the role of miR-181a-5p is consistent in prostate cancer study [48]. For miR-144-3p, researchers found that it promotes the growth and metastasis of papillary thyroid carcinoma by targeting the PAX8 gene [49].…”
Section: Discussionmentioning
confidence: 89%